Determiner Phrase in Sasaknese - Hijriati, Sartika (Universitas Muhammadiyah Mataram, 2024)
This qualitative generative syntactic study aims to discuss the forms of nominal structures and their basic patterns of a Sasak story written in 1992 published in the book “Dewi Rengganis” by applying the X-bar theory to discuss the constituent structure of nominal constructions and answering the question of whether nominal structures should be analyzed as determiner phrases or noun phrases. The result of the study shows in this language the determiners like ni ‘this’, and no ‘that’ and possessives like the suffix –na are the head that takes the noun phrase as its complement where the typical order consists of a demonstrative or articles precedes a noun, or demonstrative after the noun.